The Development of Geographic Information System - Santoso, Sugiharto Budi (Forum Geografi, 1998)
Early geographyc information systems facused on processing attribute data and geographic analysis, and had only rudimentary graphic and mapping capabilities. Phenomenal increase in computer processor speed and power in 1970s and 1980s had a major influence on GIS development. By the late 1980s, the technologies of the three main types of geo-based system had merge to various degrees. Most systems today offer powerfull capabilities for graphic production, processing of attributes, and analysis